The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/hed.26887
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating dysphagia and xerostomia outcomes following transoral robotic surgery for patients with oropharyngeal cancer

Abstract: Background: We assessed long-term patient-reported dysphagia and xerostomia outcomes following definitive surgical management with transoral robotic surgery (TORS) in patients with oropharyngeal cancer (OPC) via a cross-sectional survey study. Methods: Patients with OPC managed with primary oropharyngeal surgery as definitive treatment at least 1 year ago between 2015 and 2019 were identified. The M. D. Anderson Dysphagia Inventory (MDADI) and Xerostomia Inventory (XI) scores were compared across treatment typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“… 37 - 39 Other research exploring the effects of adjuvant treatments on dysphagia-related QOL also note unfavorable findings. 40 - 43 Specifically, a cross-sectional study of OPSCC patients undergoing TORS found that those not necessitating adjuvant therapy (n = 10) had significantly better Xerostomia Index scores and dysphagia-related QOL in the composite, physical, and emotional subdomains of the MD Anderson Dysphagia Inventory compared to those receiving adjuvant RT (n = 30) and CRT (n = 22). 40 Post-RT, dysphagia may be due to fibrosis causing poor tongue base mobility and poor contact to the posterior pharyngeal wall, impaired laryngeal elevation, and reduced vestibule and true vocal cord closure during the swallow.…”
Section: Discussionmentioning
confidence: 99%
“… 37 - 39 Other research exploring the effects of adjuvant treatments on dysphagia-related QOL also note unfavorable findings. 40 - 43 Specifically, a cross-sectional study of OPSCC patients undergoing TORS found that those not necessitating adjuvant therapy (n = 10) had significantly better Xerostomia Index scores and dysphagia-related QOL in the composite, physical, and emotional subdomains of the MD Anderson Dysphagia Inventory compared to those receiving adjuvant RT (n = 30) and CRT (n = 22). 40 Post-RT, dysphagia may be due to fibrosis causing poor tongue base mobility and poor contact to the posterior pharyngeal wall, impaired laryngeal elevation, and reduced vestibule and true vocal cord closure during the swallow.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] However, all of these studies are limited by inclusion of open surgeries or patients with HPV-negative disease, consist of small sample sizes, and have potentially omitted recent advances in radiotherapy treatment techniques. 17,18,[20][21][22] In a 2015 systematic review, Hutcheson, et al summarized the literature related to functional outcomes and found that none of the studies included in the analysis stratified patients by HPV status. These toxicities described for TMT may be less relevant for the healthier, HPV-positive population with fewer baseline comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…TMT for HPV+ OPSCC is currently viewed as a highly undesirable outcome based on evidence that it produces worse treatment‐related toxicities, including dysphagia, xerostomia, and increased feeding tube dependence when compared to primary chemoradiation alone 16–19 . However, all of these studies are limited by inclusion of open surgeries or patients with HPV‐negative disease, consist of small sample sizes, and have potentially omitted recent advances in radiotherapy treatment techniques 17,18,20–22 . In a 2015 systematic review, Hutcheson, et al summarized the literature related to functional outcomes and found that none of the studies included in the analysis stratified patients by HPV status.…”
Section: Introductionmentioning
confidence: 99%
“…2 While, to our knowledge, no phase 3 randomized clinical trials have been conducted to compare treatment modalities, retrospective studies and phase 2 trials suggest similar oncologic outcomes for these treatment approaches. 3,4 There is conflicting evidence in regard to functional outcomes with surgical vs nonsurgical approaches 5,6 ; however, patients with oropharynx cancer managed with surgery alone have more favorable swallowing outcomes, 4,7 and an increasing number of patients are being treated with upfront surgery. 8,9 Surgical approaches to the oropharynx include minimally invasive techniques with transoral laser microsurgery and transoral robotic surgery (TORS), as well as open procedures.…”
mentioning
confidence: 99%